Hot deformation characteristics of Ti43.5Al5Nb1V1Y alloy by hot press sintering. (27th November 2019) - Kang, Fuwei; Wei, Shijie; Wang, Enhao; Wang, Shanshan; Sun, Jianfei; Cao, Fuyang; Liu, Na; Zhang, Guoqing
Abstract: In this paper, Ti43.5 Al5 Nb1 V1 Y pre-alloyed powders densified by hot-pressing sintering, were prepared by gas atomization process. Isothermal hot compression simulation tests for Ti43.5 Al5 Nb1 V1 Y alloys were carried out at the conditions of deformation temperature of 1050 °C–1200 °C, strain rate of 0.001 s −1 –0.5 s −1 and deformation of 50%. The experimental results show that the flow stress change is inversely proportional to the deformation temperature, but proportional to the strain rate. The initial strain flow curves show obvious work hardening characteristics, and compared to other alloys, the dynamic recrystallization curve features of the alloy were more obvious. The hot deformation activation energy of the vacuum hot-pressing sintering Ti43.5 Al5 Nb1 V1 Y alloy is 320.861 kJ mol −1 . The experimental values of the constructed peak stress constitutive model agree well with the calculated values. Based on Prasad instability criterion and Dynamic Material Model, the hot processing map of Ti43.5 Al5 Nb1 V1 Y alloy with true strain of 0.5 is constructed, and the ideal deformation conditions are deformation temperatures of 1080 °C–1200 °Cand strain rates of 0.0015 s −1 –0.04 s −1 .